Association between body composition and aerobic capacity in karate athletes - da Silva, J. F.; Aguilar, J. A.; Moya, C. A. M.; Correia Junior, M. G. A.; dos Santos Gomes, W.; Alves de Oliveira, V. M.; Moura dos Santos, M. A.; Queiroz, D. R. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2020)
The aim of this study was to analyze the association between body composition and performance in the karate specific aerobic test (KSAT). This is a study carried out with thirteen athletes (6 females) with a mean age of 20.7 ± 4.2 years, affiliated to the Pernambuco Federation of Karate Associations, were developing this training routine during the 2018 season. Body mass and height were measured. To measure body composition, the body densitometry method was used by the x-ray double-ray absorptiometry (DEXA) technique. Karate Specific Aerobic Test was used to verify aerobic performance. Association analyzes were performed between body composition variables and KSAT performance using Pearson's correlation test and linear regression. All analyzes adopted a significance of p <0.05. KSAT performance was negatively correlated with total fat mass (r = -0.797; p = 0.001) and fat percentage (r = -0.757; p = 0.003). The linear regression model with the highest explanatory power included total fat and KSAT (adjusted R² = 0.732; p <0.001) exhibited a negative association with total fat (? = -0.21; p <0.001), and the model that included % body fat and KSAT (adjusted R² = 0.708; p = 0.003) were negatively associated with% body fat (? = -22.937; p = 0.001), both adjusted for gender and age. There is a negative association between total fat mass, body fat percentage and karate specific aerobic test performance